Asian Sudden Cardiac Death in Heart Failure (ASIAN‐HF) registry. (August 2013) - Lam, Carolyn S.P.; Anand, Inder; Zhang, Shu; Shimizu, Wataru; Narasimhan, Calambur; Park, Sang Weon; Yu, Cheuk‐Man; Ngarmukos, Tachapong; Omar, Razali; Reyes, Eugene B.; Siswanto, Bambang; Ling, Lieng H.; et al.
<x xml:space="preserve">Abstract</x> Aims Our aim is to determine mortality and morbidity in Asian patients under clinical management for heart failure (HF). Specifically, we will define the incidence of, and risk factors for, sudden cardiac death, as well as the socio‐cultural factors influencing therapeutic choices in these patients. Methods This is a prospective observational multinational Asian registry of 5000 patients with symptomatic HF (stage C) and LV systolic dysfunction (EF ≤ 40%) involving 44 centres across 11 Asian regions (China, Hong Kong, India, Indonesia, Japan, Korea, Malaysia, Philippines, Singapore, Taiwan and Thailand). Data collection includes demographic variables, clinical symptoms, functional status, date of HF diagnosis and prior cardiovascular investigations, clinical risk factors, lifestyle factors, socio‐economic status, and survey of cultural beliefs, health practices, and attitudes towards device therapy. Centre‐level characteristics (case load, referral pattern, specialization, and infrastructure) are also obtained. Patients uniformly undergo standard 12‐lead ECG and transthoracic echocardiography at baseline, and are followed over 3 years for outcomes of death or hospitalization. The mode of death and cause of hospitalization are adjudicated by a central event adjudication committee using pre‐specified criteria. Perspective By providing prospective data regarding the demographics, risk factors, and outcomes of Asian patients under treatment for HF, the ASIAN‐HF registry is expected to advance fundamental understanding of the burden and predictors of death and hospitalization among these patients. The knowledge gained will be important for guiding resource allocation and planning preventive strategies to address the unmet and growing clinical needs of patients with cardiovascular disease in Asia. Trial registration NCT01633398